Classifying severity level of postpartum depression symptom using rule based technique / Raudhah Hayati Zainuddin - Zainuddin, Raudhah Hayati (Faculty of Computer and Mathematical Sciences, 2017)
The term of “postpartum” is refer to the period occurring after childbirth with reference to the mother. Depression after giving birth is known as postpartum depression which occur during postpartum period or the literal translation means “confinement period”. This project will cover about postpartum depression in term of severity level and probabilities for each categorization of postpartum depression known as postpartum blue, postpartum nonpsychotic and postpartum psychosis based on symptom assigned by the user. This system will ease the users to avoid the burden from the negative stigma of depression since it can be use anyway and anytime they need at early sign of postpartum depression. Planning and analyzing data, design and develop system using rule based technique and evaluate the functionalities are the phases involved in project methodology using Agile method. The system are functionally tested in functionalities testing to ensure it work in well. Findings for this system, user can find their severity level of postpartum depression and probabilities for each stage of postpartum depression. This system uses XAMPP server as localhost, PHP as a programming language and MYSQL as a database. The motivation in the future is the system will expand into many kinds of disease and many fields not only for medical purpose.